Fibrólisisi Diacutánea en lesiones musculoesqueléticas - Cuviña Sánchez, Jenny Marian (2022)
ABSTRACT: This research was developed in the form of a bibliographic review, with the objective of learning about the efficacy of dicutaneous fibrolysis in physiotherapeutic rehabilitation in musculoskeletal injuries, by means of a bibliographic compilation of worldwide repositories that have scientific quality and validity. Sixty-five scientific articles were analyzed worldwide and 34 of them met the criteria for the research. The databases that contributed scientific articles were pubMed, Scopus, PEDro, Elsevier, Dialnet and Cochrane. Diacutaneous fibrolysis is a non-invasive manual technique used to treat musculoskeletal injuries that produce pain and/or restriction of movement, requiring the use of a hook that allows working on certain anatomical structures inaccessible to the physical therapist's fingers. The procedure would be purely mechanical, freeing possible adhesions between muscles and aponeurosis and between muscle and bone. A factor to be highlighted in this technique is the rapidity of its results, and it is common to find relevant favorable effects from its first application. At the end of this bibliographic research it was found that diacutaneous fibrolysis is a safe and effective technique in the short and long term for the treatment of musculoskeletal injuries, having a beneficial effect on this pathology, especially when combined with other physiotherapy techniques during treatment.